1918 how the First World War was won - Thompson, Julian 1934- (Andre Deutsch, 2018)
To commemorate the 100th anniversary of the end of the First World War, here is the rarely told story of its final, pivotal year. When the Germans launched their offensive in March, 1918, World War One changed character radically--and nowhere more so than on the Western Front. This gripping and detailed account follows that final year, examining every battle from a new, refreshing perspective: it wasn't just the British forces fighting, but also American troops and Canadian reinforcements, all masterminded by the tactical command of French General Ferdinand Foch. International in approach and filled with illustrations, it tells the story of those final violent pushes to the end of the war, and is a must-read for anyone interested in military history.